How can we prove that $\liminf x_n = -\limsup (-x_n)$?

The definitions we are using are
$\limsup x_n = \lim\limits_{n\to\infty} \sup\{x_k; k\ge n\}$
$\liminf x_n = \lim\limits_{n\to\infty} \inf\{x_k; k\ge n\}$

  • 3
    $\begingroup$ What definition of $\liminf$ and $\limsup$ do you take? What did you try? $\endgroup$ – Julien Mar 18 '13 at 20:35
  • 1
    $\begingroup$ first you need to prove that Inf (-A)=-Sup (A) $\endgroup$ – cswinson Mar 18 '13 at 20:37
  • $\begingroup$ lim Sup xn= lim (Sup {xn : n>N}) $\endgroup$ – cswinson Mar 18 '13 at 20:41

I'll go with the definition you mention. Defining $\liminf x_n$ as the smallest limit of all converging subsequences in $[-\infty,+\infty)$ and $\limsup$ as the greatest etc... would make the statement slightly easier to check.

Assume you have proved that $-\sup (-A)=\inf A$ for every subset $A$ of $\mathbb{R}$. Applying this to the set $A=\{x_n\;;\;n>N\}$ yields: $$ -\sup_{n>N}(-x_n)=\inf_{n>N}x_n\qquad \forall N. $$ Taking the limit on both sides gives the formula. Even in the case where these sequences are constant equal to $-\infty$, that is $\liminf x_n=-\infty$ and $\limsup (-x_n)=+\infty$.

Now let us prove the set property. Clearly, $A$ is not bounded below if and only if $-A$ is not bounded above. In this case, we get $-(+\infty)=-\infty$ and the property holds. Now assume we are not in the latter case. Take $a\in A$. We have $$ m\leq a\qquad\iff\qquad -a\leq -m. $$ Therefore, $m$ is a lower bound for $A$ if and only if $-m$ is an upper bound for $-A$. It follows that $-\inf A$ is an upper bound for $-A$, so $\sup(-A)\leq -\inf A$. And likewise, $-\sup(-A)$ is a lower bound for $A$, so $-\sup(-A)\leq \inf A$. This proves the equality $-\sup(-A)=\inf A$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.